Growth and yield of crops and soil quality improvement in mango based agri-horticulture system - Sahu, Sarawati; Sah, R.B.; Kumar, Abhay; P.V., Dhanyashri (Indian Journal of Agroforestry, 2022)
A field experiment was carried out in Faculty of Forestry, Birsa AgriculturalUniversity, Ranchi, Jharkhand. To study the overall scenario of growth yield and soil propertiesunder agri-horticulture system, to measure the changes under the influence of mango tree andintercrops grown in between. The experimental plots were laid out in randomized block designwith two associate cropping systems (Mango + Mustard and Mango + Linseed), sole cropping(Mango, Mustard and Linseed each) with four replications. The growth parameters of mangoviz. height, diameter, volume, crown height, crown length, crown width, crown area and yield of3 2mango were recorded 3.44 m, 12.14 cm, 0.04 m , 1.48 m, 1.95 m, 3.61 m 11.12 m and 36.68kg/tree respectively were found significantly higher in mango+mustard followed bymango+linseed and minimum in sole mango. Yield attributes of mustard, plant height, no. ofsiliqua/plant, no. of seed/siliqua and 1000 seed weight and in linseed, plant height, no. ofcapsule/plant, no. of seed/capsule and 1000 seed weight, as well as yield of mustard and linseedwere found significantly higher in sole cropping compared to mango based agri-horticulturesystem. The yield characters of mustard and linseed, such as grain yield (1072.25 and 897.00kg/ha), straw yield (2031.75 and 1487.75 kg/ha) and biological yield (3104.00 and 2384.75kg/ha) and harvest index (34.54 and 37.61 %) respectively were found significantly higher insole cropping compared to mango based agri-horticulture system. Among soil physicochemical properties, pH, phosphorus, potassium, organic carbon and water holding capacitywere at par in all the cropping systems